Homosexuality in Robbie Couch’s The Sky Blue - Vivilia Nur Alfi'ah; Yoseph Bavo Agung Prasaja (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study is about homosexuality in Robbie Couch’s The Sky Blues. This thesis aims to analyze the phenomenon of homosexuality in the novel. Qualitative research is used in this study. The problem statements are about homosexuality theory, causes, effects, and relationships between them. In the research, the analysis is conducted by using the homosexuality theory. The writer also finds that factors cause homosexuality, which covers genetics, hormonal, non-social environment, and social environment. This research also uses psychological approach, which aims to reflect the homosexual behaviors in the main character. This study focused on Sky Baker’s sexual orientation as homosexual. Boysen claims that gay men even tend to behave similarly to women, both in their interests and personality. The theory is reflected in Sky Baker’s character because he has a crush on Ali Rashid, his friend at school. The factors that make Sky Baker’s gay are caused by genetics. This study also focuses to the effects of Sky Baker’s homosexuality can be rejected by environment and can be accept by his friends. Cook explained that an over-homosexual boy has a heterosexual brother in his family. The result of habitus as homosexuality is Sky Baker has an attraction to same-sex, acts feminine, falls in love with same-sex, and fantasizes about the same sex. Homosexuality has effects on someone’s social life, including Sky Baker has been rejected by family and his school friends.